PENERAPAN APLIKASI IDENTITAS KEPENDUDUKAN DIGITAL UNTUK MENINGKATKAN EFISIENSI PELAYANAN PUBLIK DI KECAMATAN PAKAL - Harwidya Pradiptasari, Zhafirah; Ichsanuddin Nur, Dhani (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
This PkM activity discusses the Implementation of Digital Population Identity Applications to Improve the Efficiency of Public Services (IKD) in Pakal District. One of the main innovations of the Indonesian government is the introduction of the Digital Population Identity application to facilitate population data management and improve the efficiency of public administration. The purpose of this study is to analyze the implementation of the IKD application in Pakal District, Surabaya and evaluate its impact on the efficiency and quality of population administration services in the community. The method used in this study is a qualitative descriptive approach with data collection through direct observation related to public services in Pakal District to the local community, as well as conducting a survey by interviewing several people regarding the implementation of IKD and document analysis related to the implementation of the IKD application. The results of the activity show that the implementation of the IKD Application in Pakal District has a positive impact on the efficiency of population administration services, by reducing document processing time, increasing data accuracy and ease of access for the community. Based on data from the Directorate General of Dukcapil, Ministry of Home Affairs, the number of IKD activations nationally has reached 9,407,945 people, which reflects that people are increasingly finding it easier to access population documents digitally through applications on their smartphones. However, several challenges still arise, such as limited technological infrastructure and low digital literacy among some people. This study recommends increasing socialization and strengthening digital infrastructure to support the optimization of benefits regarding IKD for the community.